El Hierro (Canaries) : une île et le choix des transitions énergétique et écologique - Alain Gioda (VertigO)
The island of El Hierro (270 km2 and 8,000 inhabitants) is the most isolated in the Canary archipelago. Since June 2014, El Hierro is getting on its way toward the objective of being self-sustained with 100 % of renewable energy thanks to wind turbines mixed with a wind-powered pumped hydrostorage system using desalinated water that ensures two days of autonomy in the absence of wind or during storms. Energy independence is the result of a popular initiative supported by a technician and a political leader of the island, which was relayed by the authorities of the Canary Islands, Spain, Europe, and Unesco. However and first of all, this success of an idea like "Small is beautiful" has been developed by individual initiatives since 1947, supported by artists and the regional political party. The ecological transition was formalized in 2000 with the recognition of “Biosphere Reserve of El Hierro” by the UNESCO declaration. This allowed to raise 80 million euros which were used by a society, where local interests predominate, to build an energy complex that was projected in the 80s: a group of five wind turbines of 11MW, a desalination plant, two dams and a 11 MW hydropower plant. A good combination, in a traditional society, of the project of protection and enhancement of the nature with modernity has made possible to be in the path toward energy independence provided by renewable energy. This achievement is reproducible on the high and windy islands worldwide but mostly it can inspire many others.